Santería e "salvezza". Un approccio olistico al benessere e alle relazioni interpersonali - Alessandra Ciattini (EtnoAntropologia)
Drawing from a series of interviews to a contemporary dancer in Havana, who was initiated few years ago in the Regla de Ocha, this essay focuses on the complex relations between religion and health, intending the latter as the result of an achieved harmony between body and psyche. This theme is addressed taking into account relevant tendencies in contemporary society, which is arguably characterized by a strong and lacerating contrast – emerging in multiple variants – between utilitarian mechanistic and holistic conceptions.